A case of stercoral colitis with marked elevation of serum carcinoembryonic antigen. Issue 4 (15th February 2020) - Takehara, Kiyoto; Takehara, Yuko; Ueyama, Satoshi; Kobayashi, Tatsunori
Abstract: It should be noted that the serum CEA level can become elevated in severe stercoral colitis. Marked elevation of the serum CEA level in stercoral colitis may suggest the necessity of surgery in patients with stercoral colitis. Abstract : It should be noted that the serum CEA level can become elevated in severe stercoral colitis. Marked elevation of the serum CEA level in stercoral colitis may suggest the necessity of surgery in patients with stercoral colitis.